Enantio- and diastereoselective palladium catalysed arylative and vinylative allene carbocyclisation cascades. - Li, M; Hawkins, A; Barber, D; Bultinck, P; Herrebout, W; Dixon, D (2013)
The enantioselective synthesis of heavily decorated spirolactams has been accomplished via an arylative or vinylative allene carbocyclisation cascade. Mediated by silver phosphate, a range of allene-linked pro-nucleophiles and aryl or vinyl iodides were reacted in the presence of catalytic Pd(OAc)2 and chiral bis(oxazoline) ligands to afford the spirolactam products in good yields and high enantio- and diastereoselectivities.